Data for Permafrost Degradation Diminishes Terrestrial Ecosystem Carbon Sequestration Capacity on the Qinghai-Tibetan Plateau - Liu, Lei; Zhuang, Qianlai; Zhao, Dongsheng; Zheng, Du; Kou, Dan; Yang, Yuanhe (Purdue University Research Repository, 2021)
Dataset about the effects of permafrost degradation on C and N cycling on the Qinghai-Tibetan Plateau in the 21st century